EFFECT OF NATURAL HABITAT ON DIVERSITY OF HEMIPTERAN PREDATOR IN OIL PALM PLANTATION - Rizali, Akhmad; Himawan, Toto; Fitriani, Ima; Rahardjo, Bambang Tri; Karindah, Sri; Puspitarini, Retno Dyah; Sahari, Bandung (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Effect of Natural Habitat on Diversity of Hemipteran Predator in Oil Palm Plantation. Utillization of natural enemies in controlling oil palm pests still encounters obstacles, in particular, how natural enemies can survive and establish in oil palm plantations. The existence of natural habitats around oil palm plantations can allegedly support the occurence of natural enemies. The objective of this study was to investigate the effect of the presence of natural habitats on diversity of hemipteran predators in oil palm plantations. Field research was conducted in oil palm plantations located in Pangkalan Bun, Central Kalimantan. The plots were oil palm plantations with different distances from natural habitat i.e. near (less than 200 m), medium (about 2 km) and far (about 5 km). Each plot was selected six trees for fogging using insecticide with active ingredient lamda cyhalothrin. Based on research result, diversity of hemipteran predator in oil palm plantion was found 19 species belong to 2 families. The most dominant hemipteran predator was Sycanus sp., Eocanthecona sp. and Reduviidae sp5. The distance of oil palm plantation from natural habitat did not affect species richness, abundance and composition as well as recolonization of hemipteran predator in oil palm plantation. Abundance of hemipteran predator tend to decrease in different observation time, except Sycanus sp. Sycanus sp was likely has ability to rapidly recolonized and their occurrence were influenced by flowering vegetation in oil palm plantation.